Comparative Study Between Think Aloud and Visual Imagery in Enhancing Students’ Reading Comprehension - Siagian, Sylvania Walanda; Katemba, Caroline Victorine (LPPM Universitas Advent Indonesia, 2016)
The purpose of this study is to find out whether Think Aloud and Visual Imagery have significant difference in enhancing students’ reading comprehension. This study used comparative design, test the comprehension of the students through pre-test, treatment, and post-test. This research was done to 32 students of class 8F in Visual Imagery group; they were given passage to read and draw the image created in her mind on the paper; and 29 students of class 8E in Think Aloud group; the teacher and students think aloud the answers to the questions that were found in the text. The study was done in SMPN 1 Parongpong, West Bandung for 5 weeks or 640 minutes. Result of the study showed the average gain for Visual Imagery group is 0.038 and Think Aloud group is 0.125. The p-value = 0.686 > Î± (0.05), which means H0 is not rejected. Thus, there is no significant difference on students’ reading comprehension between those who are taught using Think-Aloud and those who are taught using Visual Imagery. Keyword: Reading comprehension, Think Aloud, Visual Imagery